Equipment for Testing Measuring Devices at a Low-Level Radon Activity Concentration - Fialova, Eliska; Otahal, Petr P S; Vosahlik, Josef; Mazanova, Monika (International journal of environmental research and public health, 2020)
The National Institute for Nuclear, Biological, and Chemical Protection, under the European project 16ENV10 MetroRADON (the European metrology program for innovation and research, EMPIR), has developed unique equipment for the testing of measuring devices at low-level radon activity concentrations. The equipment consists particularly of an airtight low-level radon chamber (LLRCH) with an inner volume of 324 liters; a Rn-222 type RF 5 flow-through source with a Ra-226 activity of 4.955 kBq developed by Czech Metrological Institute within the above-mentioned project; and a pressure vessel as a radon-free air source. The mass flow controller of the Bronkhorst EL-Flow type is a part of the apparatus and ensures the requested airflow through the radon source-partialized if necessary-through the chamber. The homogeneity of the atmosphere in the chamber is ensured by means of a continuously regulated fan (airflows in the range of 0.1-3.5 m·s-1 can be established). Another important chamber component is the measuring device of climatic conditions, since temperature, air pressure, and relative humidity must be determined. The construction of the equipment allows the time-stable radon activity concentration to be maintained at a precise level for several days. Radon concentration values can be arbitrarily and continuously set in the range from 100 Bq·m-3 to 300 Bq·m-3.
Keywords: Air Pollutants, Radioactive; radon; radon source; radon chamber; Radiation Monitoring; low-level radon activity concentration; atmosféra; radioaktivní látky znečišťující vzduch; Radon; Atmosphere; monitorování radiace; znečištění vzduchu ve vnitřním prostředí; Air Pollution, Indoor